Assessing 'approaches to learning' in Botswana, Ghana and Kenya. (March 2019) - Rolleston, Caine; Schendel, Rebecca; Grijalva Espinosa, Ana M
The concept of 'approaches to learning' (Marton, 1976) has long assumed a position of central importance in the analysis of student learning outcomes. However, constructing effective measures of students' approaches to learning is a complex task, and it is an empirical question whether such measures transfer well across contexts. In this paper, we examine the functioning of a moderately modified version of one of the most commonly used assessment of approaches to learning – the revised two-factor Study Process Questionnaire (R-SPQ2F) – in three African contexts (Ghana, Kenya and Botswana). We first present confirmatory factor analysis, which demonstrates that the modified R-SPQ2F functions in these contexts as intended by the developers of the instrument. We then consider the potential utility of the R-SPQ2F in these contexts by examining its relationship with student background characteristics, educational experiences at universities and learning outcomes.